Implementasi Metode Mind Map untuk Meningkatkan Hasil Belajar Matematika Materi Bangun Ruang bagi Siswa Kelas V SDN 29 Mataram - Musniah Musniah (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to improve student learning outcomes in learning mathematics on the material of building space using the mind map method for fifth grade students at SDN 29 Mataram. The research method used is a class action research model of Kemmis and Taggart with a spiral system cycle in which each cycle consists of planning, action, observation, and reflection. The subjects in this study were class V students, totaling 37 people. The research instruments are observation sheets, tests, and documentation. The data analysis technique used descriptive qualitative and quantitative analysis. The results showed that students' mathematics learning outcomes using the Mind Map method had increased. This is indicated by an increase in the average mathematics learning outcomes of class V students of 49.01%. In addition, the results of the analysis of observational data have increased from 46.7% to 86.7%.